A Fresh Look at Growth Oscillations in Pollen Tubes: Kinematic and Mechanistic Descriptions - Bernal-Valenzuela, R (Springer International Publishing, 2017)
Pollen tubes exhibit rapid polar growth that can display either stationary (steady) or oscillatory elongation rates. The oscillatory mode of growth provides a window into the network of interactions regulating the morphogenesis of these cells. Empirical studies of oscillatory pollen tube growth have sought to uncover the sequence of cellular events that constitute one oscillatory cycle, while other studies have attempted to formalise the principal causal interactions into computational feedback models. In this chapter, we first review the phenomenon of oscillatory tip growth from a kinematic standpoint. Three key kinematic features have emerged from our analysis: (1) oscillatory cells dominate at high elongation rates, (2) well- defined symmetrical and asymmetrical modes of oscillation are observed, and (3) the oscillation cycle of most pollen tubes unfolds over a fairly well-defined distance, independently of the average elongation rate. We then discuss some mechanistic models aiming to explain oscillatory growth and evaluate their ability to account for the observed kinematic features. Although some of these models have reached a fairly high degree of sophistication, none account for the whole range of kinematic behaviour reported in pollen tubes. We conclude with some suggestions of how current models could be improved. © Springer International Publishing AG 2017. All rights are reserved.
Keywords: Modelling; Oscillations; Pollen tube growth